Risk factors of obstetric admissions to the intensive care unit: An 8-year retrospective study. Issue 11 (March 2019) - Lin, Lin; Chen, Yan-Hong; Sun, Wen; Gong, Jing-Jin; Li, Pu; Chen, Juan-Juan; Yan, Hao; Ren, Lu-Wen; Chen, Dun-Jin
Abstract : Abstract: The aim of this study was to identify risk factors among obstetric patients admitted to the intensive care unit (ICU). The study was conducted in Third Affiliated Hospital of Guangzhou Medical University during January 1, 2009 and December 31, 2016. A total of 44, 817 pregnant women ≥20 weeks of gestational age were scanned. Demographic characteristics, perinatal outcomes, and risk factors among participants were analyzed. A number of factors (21) were more prevalent in the ICU admission group. The greatest for admission to the ICU occurred with amniotic fluid embolism, heart disease, acute fatty liver, and referral for care. The incidence of postpartum hemorrhage, hysterectomy, organ failure, and method of delivery differed significantly between groups ( P < .05). Adverse neonatal outcome differed significantly between groups ( P < .05). Complications of pregnancy are risk factors for referral to the ICU and may increase risk for unexpected outcomes among mothers and neonates.